중국 SNS기반 해외직구 앱의 지속적 사용의도에 미치는 영향 - 방사초(Shi-Chao Pang), 이종호(Jong-Ho Lee) (무역연구, 2021)
Purpose This study focuses on the influences of continuous use intention of SNS overseas direct purchase APP by following variables. Design/Methodology/Approach Through literature review, this study sorted out the main characteristics and the theory of continuous use intention of overseas direct purchase APP based on SNS. Finally, based on the APP features (Interaction, Vividness, Information Availability, Pleasure, Information Quality, Economy), Parameters (Trust, Satisfaction, Habits) and other variable(continuous use intention), the model of this study is constructed. The survey is aimed at Chinese consumers who have used SNS overseas direct-buying platforms. The questionnaire lasts for 18 days from 29 September 2020 to 16 October 2020. A total of 713 questionnaires were collected, 45 invalid documents were deleted, and 668 remaining data were statistically analyzed. Findings First, among the six characteristic factors of the direct purchase APP of SNS, all variables(Interaction, Vividness, Information Availability, Pleasure, Information quality and Economy) had significant positive impacts on satisfaction. Second, 5 independent variables except Pleasure had significant positive effects on trust. Habit playes moderating effects between two variables(satisfaction, trust) and continuous use intention. Research Implications The results show that the trust of SNS overseas direct purchase APP has the greatest influence on the continuous use intention. This study fills the gap in the research on the continuous use intention of overseas direct purchase app based on SNS. It provides a theoretical basis for consumers’ continuous use behavior. It provides knowledge and event inspiration for the continuous development of SNS overseas direct purchase APP. KCI Citation Count: 3